Metabolomic NMR Fingerprinting to Identify and Predict Survival of Patients with Metastatic Colorectal Cancer - Bertini, Ivano; Cacciatore, Stefano; Jensen, Benny V.; Schou, Jakob V.; Johansen, Julia S.; Kruhøffer, Mogens; Luchinat, Claudio; Nielsen, Dorte L.; Turano, Paola (Cancer research (Chicago, Ill.), 2012)
Earlier detection of patients with metastatic colorectal cancer (mCRC) might improve their treatment and survival outcomes. In this study, we used proton nuclear magnetic resonance (1H-NMR) to profile the serum metabolome in patients with mCRC and determine whether a disease signature may exist that is strong enough to predict overall survival (OS). In 153 patients with mCRC and 139 healthy subjects from three Danish hospitals, we profiled two independent sets of serum samples in a prospective phase II study. In the training set, 1H-NMR metabolomic profiling could discriminate patients with mCRC from healthy subjects with a cross-validated accuracy of 100%. In the validation set, 96.7% of subjects were correctly classified. Patients from the training set with maximally divergent OS were chosen to construct an OS predictor. After validation, patients predicted to have short OS had significantly reduced survival (HR, 3.4; 95% confidence interval, 2.06–5.50; P = 1.33 × 10−6). A number of metabolites concurred with the 1H-NMR fingerprint of mCRC, offering insights into mCRC metabolic pathways. Our findings establish that 1H-NMR profiling of patient serum can provide a strong metabolomic signature of mCRC and that analysis of this signature may offer an independent tool to predict OS. Cancer Res; 72(1); 356–64. ©2011 AACR.